Latest Advancements on Combating Obesity by Targeting Human Brown/Beige Adipose Tissues - Pan, Ruping; Chen, Yong (Frontiers in Endocrinology, 2022)
Obesity is defined as overaccumulation of white adipose tissue in the body, mainly under the skin (subcutaneous adiposity) or in the abdominal cavity (visceral adiposity). It could be the origin of various metabolic disorders including hypertension, hyperlipidemia, type 2 diabetes, cardiovascular diseases etc. Active adipose tissue was discovered in humans through 18F-fluorodeoxyglucose Positron Emission Tomography coupled with Computer Tomography (18F FDG-PET/CT), which was initially performed for tumor scanning. Since human active adipose tissue is probably composed of brown and beige adipose tissues and they burn white adipose tissue to generate heat, targeting human brown/beige adipose tissue to induce their thermogenic function is considered significant to combat against obesity. In this review, we describe latest advancements on promising therapeutic strategies against obesity by targeting human thermogenic adipose tissues for a further accomplishment of metabolic balance in humans.